One-Step Fabrication of Unique Mesoporous NiO Hollow Sphere Film on FTO for High-Performance P-Type Dye-Sensitized Solar Cells - Yang, Hong Bin (2016)
P-type dye sensitized solar cells (p-DSCs) deliver much lower overall efficiency than their inverse model, n-DSCs. However, they have fundamental and practical significance, in particular, their tandem structured solar cells with both p- and n-photoelectrodes could offer great potential to significantly improve the efficiency of existing solar cells. A facile and environmentally friendly method is developed to directly one-step grow hollow NiO spherical structures on fluorine-doped tin oxide (FTO) substrate, in which a Ni2+ and polymer complex spherical structure is self-constructed through a controlled solvent evaporation process, followed by calcination-converting to a unique NiO hollow sphere film. The prepared material is further used as a photocathode in p-type dye sensitized solar cells, resulting in 41% increase of an open-circuit voltage and 18% enhancement of power conversion efficiency than NiO nanoparticles photocathode. The improved performance can be ascribed to suppressed charge recombination at the photocathode/electrolyte interface. This template-free approach could be universally used to fabricate other nanostructured hollow spheres for a wide range of energy conversion applications such as electrochemical capacitors, chemical sensors, and electrochromic devices.